2001
DOI: 10.1023/a:1002869310180
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Activation of blood coagulation and thrombin formation accompany inflammation, wound healing, atherogenesis, and other processes induced by endothelial injury. Systems of hemostasis and inflammation play an important role in the pathogenesis of acute coronary syndromes. This paper reviews thrombin functions involved in its interaction with PAR family receptors, activation of platelets, endothelial cells, leukocytes, smooth muscle cells, and mast cells. Mechanisms of regulatory effects of thrombin on mast cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 104 publications
0
31
0
Order By: Relevance
“…The generation of excessive thrombin leads to thrombosis, which is the major cause of morbidity and mortality. Thrombin in close proximity to the active mediators also plays a role in the diverse cellular responses in the vascular and avascular tissues (49). It has been reported that thrombin potentiates both interferon-␥ and tumor necrosis factor-␣-induced NO production in C6 glioma cells (50).…”
Section: Discussionmentioning
confidence: 99%
“…The generation of excessive thrombin leads to thrombosis, which is the major cause of morbidity and mortality. Thrombin in close proximity to the active mediators also plays a role in the diverse cellular responses in the vascular and avascular tissues (49). It has been reported that thrombin potentiates both interferon-␥ and tumor necrosis factor-␣-induced NO production in C6 glioma cells (50).…”
Section: Discussionmentioning
confidence: 99%
“…Within the coagulation cascade, thrombin is a serine protease that also induces the activation of platelets [27]. The activation of the extrinsic coagulation pathway resulting in thrombin generation might thus support a role of platelets in CU pathophysiology.…”
Section: Pathophysiology Of Cumentioning
confidence: 99%
“…6), whereas p38 kinase inhibitor SB203580 was without effect (data not shown). It is known that upstream of the MAPK pathway the PAR-1 receptor of thrombin is coupled to both pertussis toxin-sensitive and -insensitive G proteins (5,27). In an attempt to determine whether thrombininduced CL-100 is mediated through a G i pertussis toxinsensitive G protein, we pretreated EC with 100 ng/ml of pertussis toxin prior to stimulation with TRAP-1 (100 M).…”
Section: Table I Novel Thrombin-inducible Genes In Ec Identified By Mmentioning
confidence: 99%